2020
DOI: 10.1186/s13104-020-4890-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial resistance, biofilm forming potential, and the presence of biofilm-related genes among clinical isolates of Pseudomonas aeruginosa

Abstract: Objectives: Pseudomonas aeruginosa is known as a leading cause of nosocomial infections worldwide. Antimicrobial resistance and biofilm production, as two main virulence factors of P. aeruginosa, are responsible for the persistence of prolonged infections. In this study, antimicrobial susceptibility pattern and phenotypic and genotypic characteristics of biofilm of P. aeruginosa were investigated. Results: A total of 80 clinical P. aeruginosa isolates were obtained. Isolates showed resistance to all antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 33 publications
12
92
2
Order By: Relevance
“…The smaller sized nanoparticles penetrate the bacterial cell membrane easily and damage the cellular machinery's respiratory chain. As a result, oxidative stress develops and affects the functioning of DNA and RNA paralyzing the cell division and leads to cell death ( Sandhu et al, 2018 , Muramatsu et al, 2018 , Kamali et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller sized nanoparticles penetrate the bacterial cell membrane easily and damage the cellular machinery's respiratory chain. As a result, oxidative stress develops and affects the functioning of DNA and RNA paralyzing the cell division and leads to cell death ( Sandhu et al, 2018 , Muramatsu et al, 2018 , Kamali et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a catheter for a longer period, normally over seven days, inflicts bacteriuria even after one month ( NICE, 2009 ). Bacterial biofilms are reported to be highly recalcitrant to antibiotic therapies because of multiple tolerance mechanisms ( Olivares et al, 2020 , Kamali et al, 2020 , Hrvatin, 2017 ). Kaul et al (2019) recommended alternative therapies for antibiotics to Combat Drug-Resistant Bacterial Pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The colonies are usually heavily mucoid on solid media. It has been reported that mechanisms of antimicrobial resistance in Pseudomonas strains and most bacteria include multidrug efflux pumps and downregulation of outer membrane porins, whereas virulence may include secretion of toxins and the ability to form biofilms [78,79]. A natural property of Pseudomonas is the possession of multiple mechanisms for different forms of antibiotic resistance [80], and this may have facilitated its occurrence in boreholes and sachet water.…”
Section: Pseudomonasmentioning
confidence: 99%
“…All isolates contained these genes with the exception of rpoN. Notably not identified by whole genome sequencing in this cohort were pslD, pelF, and gacS, genes previously determined to be common amongst biofilm-producing pseudomonas isolates [23,25]. Genes involved in c-di-GMP regulation are also well-established in the pathophysiology of biofilm production, but were not surveyed in this study, including siaD, nbdA, dipA, cdrA, PA4781, or PA4108 [26].…”
Section: Discussionmentioning
confidence: 85%
“…Unique to post operative endophthalmitis, intraocular foreign material, such as a lens implant can serve as a surface for bacteria to attach, and potentially as a nidus for bacteria to grow within a biofilm. Some of the most cited genes implicated in biofilm production include algD, rhlR, rpoS, and rpoN, the latter two providing anti-phagocytotic capability against host defenses [ 23 25 ]. All isolates contained these genes with the exception of rpoN .…”
Section: Discussionmentioning
confidence: 99%